Promotional Strategies for Enhancing Awareness and Acceptance of Waqf Takaful in Indonesia: A Literature-Based Study - Rafiza Zuliani; Nur Kumalahayati; Norizan Remli (Fakultas Ekonomi dan Bisnis Islam, 2026)
Waqf Takaful is a unique financial instrument within the Islamic economic system that combines the concepts of takaful (Islamic insurance) and waqf (endowment). Despite its great potential to enhance social welfare, awareness and participation in waqf takaful in Indonesia remain low. The main issue of this study concerns the effectiveness of promotional efforts in increasing public awareness and acceptance of waqf takaful among Indonesian society. A substantial gap exists between the potential and the realization of cash waqf in the country. The objective of this study is to measure the effectiveness of promotional strategies used to introduce waqf takaful and to analyze how these strategies influence public knowledge and awareness. This study adopts a qualitative approach, involving an in-depth analysis of promotional strategies implemented by waqf takaful institutions. Data were collected through literature review, interviews, and document analysis. The main findings reveal that effective promotion plays a critical role in enhancing awareness and acceptance of waqf takaful. The use of digital technology, financial innovation, and project-based approaches were found to improve promotional effectiveness. This research contributes to a deeper understanding of the role of promotion in marketing waqf takaful products. It also provides guidance for Islamic financial institutions to refine their promotional strategies and enhance public awareness and participation in waqf takaful.